IMMU-16. Next-generation CAR T-cells targeting IL13RA2 and secreting IL-15 achieve durable tumour clearance in pre-clinical model of diffuse midline glioma. (3rd June 2022) - Hotblack, Alastair; Wawrzyniecka, Patrycja; Cheng, Gordon Weng-Kit; Nannini, Francesco; Pule, Martin; Straathof, Karin
Abstract: T-cells engineered with a chimeric antigen receptor (CAR) to acquire tumour specificity provide a possible new treatment approach for childhood brain tumours. Durable clinical remissions have been achieved with CD19-directed CAR T-cells in refractory B-cell malignancies including control of leptomeningeal disease and parenchymal deposits. Early clinical data of CAR-T cells in adult glioblastoma and diffuse midline glioma (DMG) further support the rationale for development of CAR-T cell therapy for paediatric high-grade gliomas (pHGG) and other high-risk childhood brain tumours. IL13RA2 provides a suitable CAR target. It is expressed in the majority of pHGG including DMGs while expression is absent on normal (paediatric) brain tissue. Early results with CAR T-cell therapy for adult HGG has shown that IL13RA2 can be safely targeted, and potent anti-tumour activity is possible. However, responses are variable and ultimately transient. This is likely due to the immunosuppressive environment encountered by CAR T-cells at tumour sites which hampers persistent tumour-directed immunity. Here we develop a next generation CAR approach engineering T-cells with both a CAR and a cytokine signal which supports persistent anti-tumour immunity. We have generated novel IL13RA2-specific antibodies and used these to construct CARs. Using a functional screening approach assessing target-specific cytolytic function, T-cell proliferation and cytokine release, we selected the optimal IL13RA2-CAR design. Then, we generated a next generation CAR construct co-expressing inflammatory cytokine IL-15 with the IL13RA2-CAR. In a PDX model of DMG, T-cells transduced with IL13RA2-CAR IL-15, in contrast to IL13RA2-CAR alone, induced long-term tumour clearance. Further in vitro testing of IL13RA2-CAR IL-15 showed enhanced proliferation and resistance to immune-suppressive secreted factors such as TGF-β. In conclusion, co-expression of IL-15 with IL13RA2-CAR enhances CAR T-cell proliferation and in vivo persistence and achieves durable tumour clearance. IL13RA2-CAR IL-15 is being translated into a phase I clinical trial for patients with DMG.